Data Mining Approach for Feature Reduction Using Fuzzy Association Rule - Siji, PD; Valarmathi, ML (International Journal of Computer Sciences and Engineering, 2025)
Data mining is an upgrading technology for knowledge extraction in many fields like medical, educational, industrial, etc. Extracting an important data from large database is most vital factor. Data extraction processwere done through many techniques like feature extraction, prediction, classification, etc. for our research analyses prediction of data mining helps a lot for accessing useful information. In this paper we focused on road traffic dataset and we used fuzzy data extraction for membership function by using FCM. For the knowledge extraction process here we implemented the correlation and coefficient algorithm for road trafﬁc dataset and attribute reduction were done by using Genetic algorithm and finally with the help of A-Priori algorithm we generate the rule for the mining the associate object for feature reduction.